Effect of triphenylphosphate flame retardant on properties of polybenzoxazines : Research Report - Sarawut Rimdusit; Nitinat Suppakarn; Chanchira Jubsilp (Chulalongkorn University, 2014)
Chulalongkorn University. Faculty of Engineering